PENGEMBANGAN ASET KOMUNITAS DESA MELALUI PUSAT PELATIHAN PERTANIAN DAN PEDESAAN SWADAYA (P4S) BERBASIS AGRIBISNIS (STUDI KASUS DI P4S HIKMAH FARM KECAMATAN PARE, KABUPATEN KEDIRI): Kata kunci: P4S, Hikmah Farm, aset komunitas desa. - Heru Setiyadi; Vivi Nurul Choirina; Moh. Raihan Aditiya Primandito (Innofarm:Jurnal Inovasi Pertanian, 2022)
One of the organizations that supports Indonesia's agribusiness sector, particularly the supporting sub-system, is the Agricultural and Rural Training Center Self (P4S). The researcher's goal is to examine how village community assets have grown at P4S Hikmah Farm. The study took place between April and August of 2022. At P4S Hikmah Farm in Tretek Village, Pare District, Kediri Regency, the research was conducted. analysis of research data using the Miles and Huberman interactive model. The findings revealed that: 1) the Agricultural and Rural Self-Help Training Center's (P4S) development of village community assets was excellent and took full advantage of every local village potential to enhance P4S performance;2) Due to P4S's emphasis on education, training, and the development of agricultural human resources, human resource assets are very important in organizing operations; 3) Social assets in P4S Hikmah Farm are also problematic since they are linked to community empowerment, particularly for farmers.